2017
DOI: 10.1038/s41524-016-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the ab initio phase transition sequence in SrZrO3 and comparisons with SrHfO3 and SrSnO 3

Abstract: We present detailed Raman studies of SrZrO 3 (SZO) that show three anomalies in Raman modes: One has a small jump in frequency ω, one has its intensity vanish, and a third has a sharp change in temperature derivative dω(T)/dT from flat below T = 600 K to a Curie-Weiss dependence above 600 K with extrapolation to zero frequency at the known transition temperature T = 970 K, thereby proving the latter to be displacive. In addition, the P4mm ferroelectric phase predicted at high stresses has preliminary support f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Optical fiber sensors based on Raman scattering [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], Brillouin [ 16 , 17 ], and fiber Bragg grating [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] are three common ways to realize multipoint measurement. Rusen Yan et al [ 9 ] reported a temperature-dependent Raman sensor, and the temperature sensitivities are −0.011 cm −1 /K and −0.013 cm −1 /K for different modes in the range from 100 K to 320 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber sensors based on Raman scattering [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], Brillouin [ 16 , 17 ], and fiber Bragg grating [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] are three common ways to realize multipoint measurement. Rusen Yan et al [ 9 ] reported a temperature-dependent Raman sensor, and the temperature sensitivities are −0.011 cm −1 /K and −0.013 cm −1 /K for different modes in the range from 100 K to 320 K, respectively.…”
Section: Introductionmentioning
confidence: 99%